ANO1: More Than Just Calcium-Activated Chloride Channel in Cancer - Guo, Saisai; Zhang, Linna; Li, Na (Frontiers in Oncology, 2022)
ANO1, a calcium-activated chloride channel (CACC), is also known as transmembrane protein 16A (TMEM16A). It plays a vital role in the occurrence, development, metastasis, proliferation, and apoptosis of various malignant tumors. This article reviews the mechanism of ANO1 involved in the replication, proliferation, invasion and apoptosis of various malignant tumors. Various molecules and Stimuli control the expression of ANO1, and the regulatory mechanism of ANO1 is different in tumor cells. By studying the different effects of ANO1, the mechanism of tumor cell activation by overexpression of ANO1 was discussed. Current studies have shown that the expression of ANO1 is controlled by 11q13 gene amplification and may also exert cell-specific effects through its interconnected protein network, phosphorylation of different kinases, and signaling pathways. At the same time, ANO1 also resists tumor apoptosis and promotes tumor immune escape. ANO1 can be used as a good biomarker for detecting certain malignant tumors. Further studies on the channels and the mechanism of protein activity of ANO1 are needed. Finally, the inhibitors of ANO1 were discussed, which provided the research direction for the tumor-promoting mechanism of ANO1.